Communication access, public health information sources, and language preference during the COVID-19 pandemic in Indigenous communities in Northwest Territories, Canada - Rachel Harris; Fariba Kolahdooz; Afsaneh Omidimorad; Adrian Wagg; Debbie DeLancey; Kami Kandola; Sami Pirkola; Stephanie Irlbacher-Fox; André Corriveau; Sangita Sharma (PLoS ONE, 2025)
Effective communication during a public health emergency, such as the COVID-19 pandemic, has been identified by the World Health Organization as a challenge; it is also critical to ensuring more positive public health outcomes. As such, given the already limited health resources available in remote communities, this project aimed to explore communication access, sources of COVID-19 information, and language preference among Indigenous communities in Northwest Territories, Canada. Data collection occurred between April-November 2021 in ten Northwest Territories communities. Utilizing convenience sampling methods due to public health restrictions, self-identifying Indigenous adults (≥18 years) were invited to complete a semi-structured interviewer administered questionnaire. During interviews, relevant public health measures were upheld (i.e., wearing masks and maintaining distance). Open-ended questions regarding communication access, sources of COVID-19 information, and language preference were asked. Results Participants (n = 287; 31.1% male; mean age 41.6 years, SD = 13.5) reported accessing three main forms of communication: radio (84.7%), the internet (80.5%), and cable television (71.8%). Some participants (19.5%) reported having no internet access at home. Participants’ main sources of COVID-19 information were websites (35.3%), social media (26.5%), and the news delivered via television or newspaper (48.4%). Only 11.0% of participants acquired information from healthcare workers. Some participants (9.9%) preferred to receive information in the traditional languages of the Dene (Dene Ked’e, Tłıchǫ) and Anishinaabe. Ensuring communication access by providing adequate internet access in all communities and producing information sources in preferred languages should be a priority. These results can inform future public health policy for Northwest Territories.